The Complicated Economics of Prison Reform - Pfaff, John F. (2016)
Two recent books on prison growth directly address the relationship between penal change and economic conditions: Hadar Aviram’s Cheap on Crime and Marie Gottschalk’s Caught. Aviram’s is the more optimistic of the two accounts, arguing that there is at least some potential in an economic-based reform effort. Gottschalk, on the other hand, fears not only that economic-based efforts could fail to lead to significant reforms, but that they could actually make prison life worse for inmates if states cut funding and support without cutting populations. Both books make many provocative points, but both also suffer from some surprising omissions. Ultimately, both books, and Gottschalk’s in particular, are likely too pessimistic about economic-based reform, although for reasons that neither book adequately addresses. I focus on two major themes in this Review. First, what exactly is the relationship between the current fiscal crisis and prison reform? The second issue I consider is narrower: the impact of private prison firms on prison reform